Peningkatan Produktivitas Pelayanan Pemancingan Tepian Sungai Siak Berbasis Mobile bagi Kelompok Usaha Rumah Pancing : Pengabdian - Sunaryo, Sunaryo; Israyandi, Israyandi; Meirizha, st. Nova (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
In terms of potential, the people of Palas Village mostly depend on the agricultural sector, industrial employees and fisheries in the river basin (DAS). One of the local potentials that is quite prominent is the existence of a Fishing Park on the banks of the Siak River (SUSI). With 6 floating houses and 2 fishing boats, it can improve the decent life for partners by seeing changes in their increasingly improving economic growth so that the sustainability of this program can be carried out in such a way. Implementation in the form of intensive implementation and assistance to produce mobile-based floating house empowerment products. The activities that have been carried out are the manufacture of 5 floating houses for a size of 2x2 meters and 1 unit with a size of 3x5 meters, as well as one unit of fiber boat made from new with a 7.5 Hp engine and repair of 1 unit of 20 Hp capacity boat, as well as the installation of a 100Wp solar panel lighting system and financial management and asset management training have also been carried out as well as social media-based marketing training.